Neoliberalism for the Common Good? Public Value Governance and the Downsizing of Democracy. (7th May 2014) - Dahl, Adam; Soss, Joe
<x xml:space="preserve">Abstract</x> This article raises a set of cautions regarding public value governance along two dimensions. First, it questions the common claim that public value governance poses a direct challenge to the economistic logic of neoliberalism. Second, although public value is often presented as a democratizing agenda, leading works sidestep foundational questions of power and conflict and advance prescriptions that are at odds with important democratic values. Without attending to these problems, the public value concept risks producing a new variant of neoliberal rationality, extending and strengthening the de‐‐democratizing, market‐oriented project that its proponents seek to overturn.